THE ROLE OF FAIRY TALES IN CHILDHOOD DEVELOPMENT - Mirsaidova Nilufar Sobirjonovna (Journals Park Publishing, 2024)
This topic explores the significance of fairy tales in shaping childhood development. Fairy tales have been a staple in children's literature for centuries, serving as a source of entertainment, moral lessons, and imaginative stimulation. Understanding how fairy tales impact cognitive, emotional, and social development in children can provide valuable insights into their overall well-being
Keywords: Fairy tales, childhood development, literature, moral lessons, imagination, cognitive development, emotional development, social development.